Exploring in-vitro antioxidant, cytotoxicity, hemolytic, thrombolytic and anticancer potentials of Ochthochloa compressa (Forssk.) Hilu - Muhammad Atif; Mirza Imran Shahzad; Muhammad Younus Khan; Tahir Maqbool; Jawaria Aslam; Faheem Hadi; Gildardo Rivera; Abdul Rauf (PLoS ONE, 2025)
Background Globally, medicinal plants are found therapeutically very effective against many illnesses. Still there is huge demand of plant based alternate medicines in market. The therapeutic potential of many plants is still unexplored. One such medicinal plant is Ochthochloa compressa, a member of family Poaceae commonly located in Cholistan desert of Bahawalpur, Pakistan. Purpose The purpose of this study is to evaluate some pharmacological properties of plant which include; exploration of cytotoxic, hemolytic, antioxidants, anticancer and thrombolytic phytochemicals from various extracts of O. compressa. Study Design This study includes in-vitro experimental study design. Methodology O. compressa extracts were prepared on the basis of polarity. The extracts were subjected for screening of phytochemicals and determining the total bioactive contents. Each extract was tested for cytotoxicity, hemolytic, antioxidant, thrombolytic and anticancer potential through cytotoxic and cell viability assays; MTT, morphology, crystal violet, trypan blue and scratch. GCMS analysis of each extract was done for identification of phytocompounds. In-silico molecular docking was performed against phytocompounds of EtOAc extract and further studied to visualize interactions between the compounds and coagulation factor XI. Compounds which showed maximum binding affinity were used in ADMET studies. Results The phytochemical screening and GCMS analysis revealed various phytochemicals in plant extracts. HET CAM assay revealed that all extracts were non and/or weak irritant except DCM which was moderately irritant. The least hemolytic activity was observed in all extracts, which proved that the plant is non-toxic, non-hemolytic and safe to use. The extracts showed a good antioxidant potential and order was as; MtOH > Aq > n-Hex > EtOAc > DCM. Promising anticancer potential was observed by extracts of this plant against HepG2 cell line and order of activity was as; n-Hex > MtOH = Aq = DCM > EtOAc. Notably high thrombolytic potential was observed by all extracts especially from EtOAc (96.2 ± 0.88) which was almost equal to Streptokinase (99.3 ± 0.41). Phytocompounds of EtOAc identified by GCMS analysis showed significant binding affinity with coagulation factor XI protein, and upon evaluation of ADMET profile, all compounds followed Lipinski’s rule of five, being suitable for orally administration. Conclusion O. compressa extracts are good source of antioxidant, anticancer and thrombolytic agents. The plant is non-toxic and non-hemolytic as well.